2016
DOI: 10.1111/jcpt.12391
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of topiroxostat and allopurinol in Japanese hyperuricemic patients with or without gout: a phase 3, multicentre, randomized, double‐blind, double‐dummy, active‐controlled, parallel‐group study

Abstract: What is known and objective: There are no clinical reports that have compared topiroxostat, a selective xanthine oxidase inhibitor, with allopurinol in serum urate-lowering efficacy. The aim of this study was to compare the efficacy and safety of topiroxostat and allopurinol in Japanese hyperuricemic patients with or without gout. Methods: A phase 3, multicentre, randomized, double-blind, double-dummy, active-controlled, parallel-group study conducted in Japan. Patients who had inadequate serum urate levels (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…It has been reported that febuxostat reduces UA more effectively than allopurinol, 7 while the reduction of UA by topiroxostat and allopurinol is reported to be similar. 8 In our previous study, febuxostat not only reduced UA more rapidly than allopurinol, but also achieved significantly lower s-Cr, eGFR, urinary albumin, cystatin-C, O-LDL, and hs-CRP compared with allopurinol. 5, 6 Given that the patient demographic profile differed between our previous study and the present study, head-to-head comparison is not appropriate.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It has been reported that febuxostat reduces UA more effectively than allopurinol, 7 while the reduction of UA by topiroxostat and allopurinol is reported to be similar. 8 In our previous study, febuxostat not only reduced UA more rapidly than allopurinol, but also achieved significantly lower s-Cr, eGFR, urinary albumin, cystatin-C, O-LDL, and hs-CRP compared with allopurinol. 5, 6 Given that the patient demographic profile differed between our previous study and the present study, head-to-head comparison is not appropriate.…”
Section: Discussionmentioning
confidence: 75%
“…8 No study, however, has compared febuxostat with topiroxostat. Accordingly, a clinical study was conducted to compare febuxostat with topiroxostat and assess potential differences in efficacy (TopiROxostat and FEbuxostat in a randomized, Open-label, cross-over trial for hyperuricemia with cardiovascular disease (TROFEO trial).…”
mentioning
confidence: 99%
“…Hosoya et al 5) reported similar overall incidence of adverse events and drug reactions between topiroxostat and allopurinol groups from baseline to 4 months. Topiroxostat was well tolerated in our study and was continued over 16 months.…”
Section: Fig 1 Changes In Serum Ua Levels During the Observation Pementioning
confidence: 83%
“…4) In a multicenter, double-blind randomized controlled trial comparing the XO inhibitors topiroxostat 120 mg/d and allopurinol 200 mg/d in Japanese hyperuricemic patients with or without gout, topiroxostat showed a non-inferior decrease in serum UA levels compared with allopurinol and was well tolerated (change in serum urate levels of −36.3 vs. −34.3%, respectively). 5) In another study involving hyperuricemic stage 3 CKD patients with or without gout, topiroxostat 160 mg reduced serum UA levels (−45.3%) and urinary albumin-to-creatinine ratio (−33.0%) over 22 weeks. 6) Also, in HD patients receiving topiroxostat therapy, serum UA levels were reduced from 9 to 5 mg/dL and the serum concentrations of topiroxostat were 25 ng/mL before HD sessions.…”
mentioning
confidence: 98%
“…vascular injury and renal dysfunction [7,8]. Topiroxostat, a selective xanthine oxidoreductase inhibitor, is used for the management of hyperuricemia in patients with or without gout in Japan [9][10][11]. Topiroxostat not only effectively reduced SUA levels, but also had a urinary albumin-to-creatinine ratio (UACR)-lowering effect in hyperuricemic stage 3 chronic kidney disease patients [12].…”
Section: Introductionmentioning
confidence: 99%